If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying (u^{3}+ -8) + -3u + 8 = 0 Reorder the terms: (-8 + u^{3}) + -3u + 8 = 0 Remove parenthesis around (-8 + u^{3}) -8 + u^{3}+ -3u + 8 = 0 Reorder the terms: -8 + 8 + -3u + u^{3}= 0 Combine like terms: -8 + 8 = 0 0 + -3u + u^{3}= 0 -3u + u^{3}= 0 Solving -3u + u^{3}= 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), 'u'. u(-3 + u^{2}) = 0## Subproblem 1

Set the factor 'u' equal to zero and attempt to solve: Simplifying u = 0 Solving u = 0 Move all terms containing u to the left, all other terms to the right. Simplifying u = 0## Subproblem 2

Set the factor '(-3 + u^{2})' equal to zero and attempt to solve: Simplifying -3 + u^{2}= 0 Solving -3 + u^{2}= 0 Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + u^{2}= 0 + 3 Combine like terms: -3 + 3 = 0 0 + u^{2}= 0 + 3 u^{2}= 0 + 3 Combine like terms: 0 + 3 = 3 u^{2}= 3 Simplifying u^{2}= 3 Take the square root of each side: u = {-1.732050808, 1.732050808}## Solution

u = {0, -1.732050808, 1.732050808}

| 17x-3=10x-38 | | 6(2x+x)(x-28)=0 | | x-7.3=6.1 | | 0.16=2x | | (5v-1)(8+v)=o | | (5v-1)(8+v)=0 | | 6(2x+7)(x-4)=0 | | 3t+14=-6t-13 | | 3=5x-8 | | -4y+5=35 | | x+3x+-x+8=5x-x+4 | | 5x+3y=27 | | 6x+4=44 | | 11x=220 | | 2L^2-5L=52 | | 64=c-23 | | 2y-6-6y+y=-18 | | 152=r+86 | | 10=5-6.5 | | 6b-3=39 | | x/5=x/6+8 | | 32=2n+10 | | 0.5n+2=-7 | | -2x^6-6x^5+56x^4=0 | | 49a^2-64f^2=0 | | c^2-12c+36=0 | | (x-18)/6+(x+9)/9=x+5 | | 10-5x-7-10x=6 | | 13x-4+9x+16=180 | | -6=3.1t+6.4 | | 9y+10=19 | | h(x)=6 | | 6n-19=53 | | 50=5c-10 | | 4k-42=18 | | 19d-1=56 | | -5(2x-7)+2=-10x+37 | | 3n+6.2=9.2 | | 4t-1.8=10.6 | | 10.2=6t-1.2 | | 5x=3+2x | | 6s-5.1=18.9 | | 10x+3=4x+15 | | 2x^2+13xy+18y^2=0 | | 4x^2+xy-18y^2=0 | | 0=2(9x^2-17x-2) | | -4w^2+w+5=0 | | 2x^2-17xy+35y^2=0 | | 2w^2+2w+8=16 | | -3y^2+14y+24=0 | | x^2+2x+8=6 | | 5x+14=7(x+2)-2x | | 4x^2-13xy-12y^2=0 | | x(a+b)=c | | r^2+3r-18=0 | | 7(3x-1)=-91 | | 0=-16t(t-9)(t+9) | | 10x^2-19x+11=0 | | 6u^2+11u+16=0 | | 150=2x | | (6x-7)=-17+6x | | s^2=-10-7s | | 12(2x+3)(x-2)=0 | | 6y^2+11y+16=0 | | 2x+30+4x-50=180 |